2021
DOI: 10.2147/jpr.s325059
|View full text |Cite
|
Sign up to set email alerts
|

Pain Relief Salvage with a Novel Minimally Invasive Posterior Sacroiliac Joint Fusion Device in Patients with Previously Implanted Pain Devices and Therapies

Abstract: Background Sacroiliac joint (SIJ) pain is a common cause of low back pain, a problem experienced by two-thirds of adults in the United States population. Traditionally, the management of persistent SIJ-related pain has involved conservative therapies (physical therapy, topical medications, oral anti-inflammatory medications), interventional therapies (SIJ steroid injections or ablation), and surgery (SIJ fusion; open and lateral approach). Recent advancements in technology have paved the way for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…This multi-institutional review demonstrates that patients with persistent sacroiliitis despite usual medical management review of patients with a history of previously implanted pain devices and therapies receiving a posterior MI SIJ fusion device as a salvage therapy resulted in a mean patient reported pain relief of 67.6%. 19 Similar to these studies, our cohort reported an overall patient reported pain relief of 66.5% and NRS reduction of at least 3, over a year out from initial implant. Notably, patients in this review reported relief that was sustained on average 612 days after implant.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This multi-institutional review demonstrates that patients with persistent sacroiliitis despite usual medical management review of patients with a history of previously implanted pain devices and therapies receiving a posterior MI SIJ fusion device as a salvage therapy resulted in a mean patient reported pain relief of 67.6%. 19 Similar to these studies, our cohort reported an overall patient reported pain relief of 66.5% and NRS reduction of at least 3, over a year out from initial implant. Notably, patients in this review reported relief that was sustained on average 612 days after implant.…”
Section: Discussionsupporting
confidence: 81%
“… 18 A recent publication by Deer et al detailed a retrospective chart review of patients with a history of previously implanted pain devices and therapies receiving a posterior MI SIJ fusion device as a salvage therapy resulted in a mean patient reported pain relief of 67.6%. 19 Similar to these studies, our cohort reported an overall patient reported pain relief of 66.5% and NRS reduction of at least 3, over a year out from initial implant.…”
Section: Discussionsupporting
confidence: 81%
“…This subset of patients reported 76.5% pain relief with an average follow-up duration of 394.4 days. 17 There were no device related major adverse events or complications in either study.…”
Section: Introductionmentioning
confidence: 79%
“…Deer et al published a case series on the utilization of posterior SIJ fusion as a salvage technique in patients who had previously undergone advanced interventional pain therapies. 17 A total of 111 patients with history and physical exam consistent with SIJ pathology who had previously undergone spinal cord stimulation, interspinous spacer, intrathecal drug delivery, or minimally invasive lumbar decompression and had persistent LBP were studied. The mean patient reported pain relief following SI joint fusion was 67.5% following implant at last follow-up, which was on average 290 days from the date of implant for the index area of pain.…”
Section: Introductionmentioning
confidence: 99%
“…While previous investigators have reported efficacy of 66.5% to 76.5% in pain reported outcomes for this approach, there are currently no studies that clinically examine the consistency of the allograft placement. 39 , 41 …”
Section: Discussionmentioning
confidence: 99%